THE EFFECT OF ADDITION OF TAXPAYERS NUMBER, TAX AUDIT, TAX BILLING, AND TAXPAYERS COMPLIANCE TOWARD TAX REVENUE - Waluyo Waluyo (The Accounting Journal of Binaniaga, 2016)
The purpose of this research is to examine the effect of addition of Taxpayer Number, Tax Audit, Tax Billing and Taxpayer Compliance toward tax revenue in simultaneously and partially. This research is done by using a multiple linear regression analysis model. The object of this research are tax office Tigaraksa for the period of 2009-2012. Data are collected from annual report of Tax Office Tigaraksa for the period of 2009-2012, consist of the number of additionaltaxpayer, number ofeffectivetax payers, the realization oftax assessments, the amount oftax arrears,number ofactual disbursement oftax arrears,tax revenue target,tax revenue, andthe reportednumber oftax returns. The results of this research are (1) increasing the number of taxpayers effect on tax revenue, (2) tax audit effect on tax revenue, (3) tax billing has no effect on tax revenue, (4) tax compliance effect on tax revenue, (5) the addition of the taxpayer, tax audits, tax billing and tax compliance simultaneously affect the tax revenue.Keywords: Addition Taxpayer Number, Tax Audit, Tax Assessment, Tax Compliance, Tax Revenue.